Initial Interview Checklist Increases Counsellor Effectivenss - Vriend, John; Kottler, Jeffrey (Canadian Journal of Counselling and Psychotherapy, 2012)
A structure is described for use by practicing counsellors and trainees to help them systematically conduct initial interviews including all significant data gathering and process component variables. A checklist is suggested as a practical way in which practitioners may sequentially address key points.